2008
DOI: 10.1007/s10709-008-9334-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture underlying convergent evolution of egg-laying behavior in a seed-feeding beetle

Abstract: Independent populations subjected to similar environments often exhibit convergent evolution. An unresolved question is the frequency with which such convergence reflects parallel genetic mechanisms. We examined the convergent evolution of egg-laying behavior in the seed-feeding beetle Callosobruchus maculatus. Females avoid ovipositing on seeds bearing conspecific eggs, but the degree of host discrimination varies among geographic populations. In a previous experiment, replicate lines switched from a small ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Even after a few hundred generations in the laboratory, selection experiments in multiple laboratories have shown that this population maintains heritable variation for fitness‐related traits (e.g. Messina & Karren, ; Messina, ; Fox et al ., ; Lind et al ., ; see also Magalhães et al ., ). We kept stock cultures and conducted all experiments in a growth chamber at 24 °C and constant light.…”
Section: Methodsmentioning
confidence: 98%
“…Even after a few hundred generations in the laboratory, selection experiments in multiple laboratories have shown that this population maintains heritable variation for fitness‐related traits (e.g. Messina & Karren, ; Messina, ; Fox et al ., ; Lind et al ., ; see also Magalhães et al ., ). We kept stock cultures and conducted all experiments in a growth chamber at 24 °C and constant light.…”
Section: Methodsmentioning
confidence: 98%
“…The Burkina Faso (BF) population is adapted to the larger cowpeas; larvae are scramble competitors and crowded seeds frequently yield multiple adults. Females are less deterred from egg laying by the presence of previously laid eggs, lay small eggs and exhibit fairly high size‐adjusted fecundity (Fox et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
“…At least some of the differences between the African and Asian populations appear to depend on the different properties of their respective hosts (Messina and Karren 2003, Messina 2004a, Fox et al 2009). The African population was collected in Burkina Faso from an infestation of cowpea, Vigna unguiculata (L.) Walpers (Messina 1993), and has been continuously reared on that host.…”
mentioning
confidence: 99%